Cooperation and Commitment of Parents and Teachers in Developing Students' Religious Character - Sayfriyon, Sayfriyon; Halim Hanafi, Abdul; Kamal, Thamrin (Islamic Studies in the World, 2024)
Background. National education aims to form the character of students, and among the characters that must be fostered is religious character, and to develop religious character cannot be completely handed over to teachers and educational institutions, collaboration between parents and teachers in fostering religious character is needed. Purpose. This study aims to uncover and analyze related to the forms of cooperation carried out by parents and teachers in fostering students' character, and also examine how committed parents are in fostering religious character in the family environment. Method. The method used in this study is qualitative descriptive, this method is in line with the purpose of the research which will analyze data in the form of words and sentences, the data source is teachers and several parents, data is collected through observation, interviews and documentation studies. Data analysis is carried out since data collection, data classification, to draw conclusions. Results. The results of the research are that there are several forms of collaboration between parents and institutions in fostering the religious character of students in Islamic Elementary School, especially Adzkia, namely parenting education, communication, volunteering, learning in the home environment, and worship activities.